Digital Transformation in Residential Property Management in Prague - Hopfgartner, Georg Anton; Sadílek, Tomáš; Linzatti, Michaela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis examines how digital management systems can replace or complement traditional residential property management in Prague. Using a single-case study of PS Group, a medium-sized property owner and manager, it analyses two embedded units: (1) technical management of a 45-flat portfolio and (2) rent setting in a newly developed 21-unit residential building in Smíchov. The research combines internal operational data (complaint logs, working-time records, rent rolls and cost data), supplier offers for IoT and metering solutions, and expert interviews with internal managers and external PropTech providers. Descriptive statistics and cost–benefit analysis are applied to quantify labour savings and technology costs, while external rent benchmarks (FlatZone) are used to evaluate pricing performance. The findings show that approximately 61% of technical maintenance time is at least partially digitalisable, but a full-scale IoT and digital-twin solution is not yet economically attractive for a small residential portfolio with many units under warranty. By contrast, low-cost software tools, such as tenant communication platforms and professional rent data analytics, deliver a clearly positive net benefit and help avoid substantial pricing mistakes in thin, high-value segments. The thesis concludes that “light” digitalisation—focused on communication, workflow structuring and data-driven pricing—currently offers the best balance between efficiency gains, organisational complexity and investment risk for SME property managers in Prague.
Vedoucí práce: Tomáš Sadílek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses